Prediction of Post-Traumatic Growth Based On Sensitivity to Rejection and Resilience in Adolescents with Divorced Parents - Sadat Nazemi Dehkharghani, Darya; Khabir, Leila (International Journal of Applied Behavioral Sciences, 2024)
Background and Aim:Parental divorce is one of the most stressful events that teenagers face, and it leaves short-term and long-term economic, social, and emotional effects on teenagers. The purpose of this research is to predict the posttraumatic growth based on sensitivity to rejection and resilience in adolescents who have experienced parental divorce. Materials and Methods:The research implementation method was correlation type. The sample studied were teenagers aged 13 to 17 in Kerman who had experienced the divorce of their parents and had referred to counseling centers (Jomhuri Blvd, EmamJomeh, and HezaroyekShab Street) in Kerman. After the screening and using the available method after visiting the counseling centers in Kerman, the researcher selected 100 people who met the inclusion and exclusion criteria. Data collection was based on Sarmad et al.’s sensitivity to rejection questionnaire, Connor and Davidson’s resilience questionnaire, and Tedeschi and Kalon’s post-traumatic growth questionnaire. The analysis and information obtained from the implementation of the questionnaire were checked through SPSS software version 26 and the data was analyzed using a simple regression inferential test. Results:The value of the standardized regression coefficient (BETA)for sensitivity to rejection is equal to0.165 and for resilience is equal to0.911. According to the value of the t statistic obtained, which is significant at the alpha level of0.01, the research hypothesis is confirmed. Conclusion:The research results showed that sensitivity to rejection negatively and significantly predicts post-traumatic growth in teenagers with divorced parents, and resilience positively and significantly predicts post-traumatic growth in teenagers with divorced parents